25th AIAA/CEAS Aeroacoustics Conference 2019
DOI: 10.2514/6.2019-2454
|View full text |Cite
|
Sign up to set email alerts
|

Eddy viscosity for resolvent-based jet noise models

Abstract: Response modes computed via linear resolvent analysis have shown promising results for qualitatively modeling both the hydrodynamic and acoustic fields in jets when compared to data-deduced modes from high-fidelity, large-eddy simulations (LES). For an improved quantitative prediction of the near-and far-field, the role of Reynolds stresses must also be considered. In this study, we propose a methodology to deduce an eddy-viscosity model that optimally captures the nonlinear forcing of resolvent modes. The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…These references and others have shown that including an eddy viscosity substantially improves the predictive capabilities of linearized models of the Navier–Stokes equations for wall-bounded flows, and recent work has shown similar benefits for free-shear flows (Pickering et al. 2019). Of particular relevance, Morra et al.…”
Section: Examplesmentioning
confidence: 78%
“…These references and others have shown that including an eddy viscosity substantially improves the predictive capabilities of linearized models of the Navier–Stokes equations for wall-bounded flows, and recent work has shown similar benefits for free-shear flows (Pickering et al. 2019). Of particular relevance, Morra et al.…”
Section: Examplesmentioning
confidence: 78%
“…The influence of viscosity in the linear operator, A m , has previously been based upon the molecular viscosity, Re j , however, recent resolvent analyses incorporating an eddyviscosity model, Pickering et al (2019) for turbulent jets and Morra et al (2019) in channel flow, have shown substantial improvement for SPOD-resolvent comparisons. Thus, we proceed by including an eddy-viscosity model based upon the turbulent kinetic energy (TKE) suggested for turbulent jets by Pickering et al (2019). This model was primarily chosen due to its simplicity and availability of the corresponding quantities from the LES database.…”
Section: Resolvent Analysismentioning
confidence: 99%
“…l m is chosen as the width of the shear layer where the turbulent kinetic energy is more than 10% of its maximum value at each streamwise location, and the scaling constant c = 0.0065 is used considering the favorable SPOD-resolvent alignments previously shown over m = 0 − 3 and St = 0.05 − 1. With the inclusion of an eddy-viscosity model the forward operator becomes Pickering et al (2019)). The discretization scheme and boundary condition treatment are the same as those used in Schmidt et al (2018) and refer the reader to that paper for further numerical details.…”
Section: Resolvent Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, eddy viscosity models have been included in the linear operator. This can enhance the extent to which the resolvent modes match the observed turbulence structure (Cossu et al 2009;Hwang & Cossu 2010;Morra et al 2019;Pickering et al 2019). However, physical interpretation of the remaining, unmodelled forcing terms then becomes unclear, as the use of an eddy viscosity amounts to a partial modelling of the effects of nonlinear forcing from Reynolds stress fluctuations.…”
Section: Introductionmentioning
confidence: 99%